2020
DOI: 10.3390/ani10020180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with Combination of Tributyrin and Essential Oil on Gut Health and Microbiota of Weaned Piglets

Abstract: The aim of this study was to determine the effects of dietary inclusion of the combination of tributyrin with oregano or methyl salicylate as a substitute to antibiotics on gut health and microbiota of piglets. A total of 48 weaned crossbred piglets (Duroc × Large White × Landrace, 8.79 ± 0.97 kg, 21 ± 1 d) were randomly allocated to four experimental groups and fed for 4 weeks: the basal diet (Con); the control plus antibiotics (AB); the control plus oregano and tributyrin (OT); and the control plus methyl sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Tributyrin also reduces diarrhoea due to its nutrient absorption, and the intestinal morphology of villi enhancement in weaned piglets [54]. Tributyrin and butyric acid lower the pH of GIT (particularly in the stomach and intestine) promoting an increase in beneficial bacteria [32].…”
Section: Serum Metabolic Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Tributyrin also reduces diarrhoea due to its nutrient absorption, and the intestinal morphology of villi enhancement in weaned piglets [54]. Tributyrin and butyric acid lower the pH of GIT (particularly in the stomach and intestine) promoting an increase in beneficial bacteria [32].…”
Section: Serum Metabolic Profilementioning
confidence: 99%
“…Tributyrin can act as a histone deacetylase inhibitor (HDAC), stimulating muscle growth through satellite cell differentiation in muscular tissue promoting animal performance [31]. In addition, butyrate supplementation may increase villus height and crypt depth in the duodenum [32]. Antibacterial activity related to butyrate was observed through a reduction in intestinal pH and a decrease in harmful bacteria in the caecum [33].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous study, tributyrin at dosage of 1.4 g per kilogram combined with oregano essential oil (OT) or methyl salicylate (MT) respectively 0.6 g per kilogram in powered form may have beneficial effects at the intestinal level of piglets, including the morphological structure and microbiota communities [ 12 ]. However, both treatments did not show significant differences in performance parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, tributyrate glyceride, also called tributyrin, appears to be a good candidate for alleviating intestinal dysfunctions, modulating immune response and improving growth performance in piglets. Despite the large number of papers addressing tributyrin impact on weaning piglets, its efficacy as a growth promoter is sometimes controversial [ 13 , 14 , 15 , 16 ] probably because of different experimental conditions in farm trials. Indeed, the efficiency of tributyrin, as with all other growth promoter candidates, may vary based on its mechanisms of action, the basal diet composition and the animal’s health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological changes of the intestinal mucosa are one of the impacting factors on the animal’s welfare, and some studies indicated that tributyrin could alleviate these weaning-related symptoms. In particular, tributyrin demonstrated effectiveness in modifying crypt depth and villus height in different intestinal sections [ 13 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%